Identification of inorganic elements in egg shell of some wild birds in Baghdad: Faris A. Al-Obaidi1 , Basim I. Mehdi2 and Shahrazad M. Al- Shadeedi3 - Al-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2012)
The objective of this study is the identification of inorganic elements in egg shell of some wild birds including House Sparrow, White- eared Bulbul, Collared Dove and Rock Dove. Samples of eggs from these birds were collected from Baghdad city during 2011. Egg shell were analysed for ash, macro-elements and micro- elements including Ca, P, Mg, Fe, K, Mn, B, Zn, Co, Cr and Pb. The findings revealed that the ash percentage was high in egg shell of all birds under study which were consecutively 1.73, 1.72, 1.79 and 1.78 % for House Sparrow, White- eared Bulbul, Collared Dove and Rock Dove, Ca percentage was the highest percentage among the other elements which were 97.3, 97.4, 97.8 and 97.8 % respectively, where as P and Mg were ranging between 0.85 and 0.89 %. Shells of House Sparrow eggs were high in Cr, at the same time, the shells of White- eared Bulbul eggs were high in K, and those of Collared dove and Rock dove were high in Fe, Mn, and B. Percentage of Pb in egg shell of all studied birds were low.